Engendered Expressions of Anxiety: Men’s Emotional Communications With Women and Other Men - Gough, Brendan; Robertson, Steven; Luck, Hannah (Frontiers in Sociology, 2021)
While the contemporary therapeutic discourse inveigles us to talk about our personal problems, a countervailing neo-liberal healthist discourse, aligning with conventional masculinity norms, presumes that we will manage any issues independently. This discursive tension can be difficult to navigate, especially for men confronted with still powerful traditional expectations around masculinity (e.g. self-reliance; personal control; restricted emotionality). Although qualitative research has examined how men negotiate masculinities with respect to depression, to date there has been scant attention focused on men experiencing anxiety. This article reports on an interview study with men, some with anxiety diagnoses and some without (N=17). Thematic analysis highlights that participants can and do talk about their anxieties, most readily with significant women in their lives (e.g. partners; mothers) – although this is not always straightforward. Talking to other men was more fraught, and while participants were wary of sharing problems with male friends, or signalled issues indirectly, they also highlighted situations where they would open up e.g. workspaces where they felt safe; with best friends. Those who had gone through a therapeutic process over many years tended to me more comfortable talking to others, male or female, about their mental health – and were also keen to other support to others where they could. Our analysis suggests that despite stereotypical notions of silent, self-contained men, there are many contexts where men may feel comfortable sharing their stories of pain and suffering. This chimes with wider cultural changes and the reported experiences of some mental health initiatives.